A mitochondria-targeted fluorescent probe for fast detecting hypochlorite in living cells. (May 2020) - Li, Hongfang; Miao, Yu; Liu, Zhixue; Wu, Xue; Piao, Chunxiang; Zhou, Xin
Abstract: A fast-responsive fluorescent probe PI-Py was designed and synthesized for sensitive and selective detecting hypochlorite (ClO − ). The probe PI-Py was intrinsically non-fluorescent due to the PET effect of the phenothiazine moiety. After reacting with ClO −, the PET effect was blocked, and a strong green emission of the BODIPY unit was recovered. The probe PI-Py showed an excellent selectivity towards ClO − in comparison of other ROS. The limit of detection for ClO − was calculated to be 1.7 nM, proving the probe's high sensitivity. Moreover, the probe PI-Py has been proved to be effective in visualizing the variations of exogenous ClO − in living HeLa cells. A co-localization study employing Mito Tracker red reveals that the PI-Py is specifically located in the mitochondria. Graphical abstract: A new BODIPY-based fluorescent probe for ClO − was developed successfully. This probe can be used in visualizing the changes of exogenous ClO − in the mitochondria. Image 1 Highlights: A novel BODIPY-based fluorescent probe PI-Py was synthesized. The probe PI-Py showed an excellent selectivity and sensitivity towards ClO − . Fluorescent titrations, MS spectra support a PET OFF-ON mechanism. Living cells imaging for exogenous ClO − located in the mitochondria was observed.